2016
DOI: 10.1177/2150135116673809
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Results of Sinus of Valsalva Aneurysm Repair

Abstract: In this relatively high-risk population, repair of SVA can be achieved with satisfactory early results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“… 1 In children, rupture of sinus of Valsalva aneurysms is rare. 3 There are reports of syndromic children, one of a boy with mosaic trisomy 13. 6 …”
Section: Discussionmentioning
confidence: 99%
“… 1 In children, rupture of sinus of Valsalva aneurysms is rare. 3 There are reports of syndromic children, one of a boy with mosaic trisomy 13. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Polos et al 7 performed a valve-sparing root reconstruction procedure(remodeling technique)for an SVA and Carlotta et al 8 conducted an aortic valve repair using a hemi-remodeling technique. However, Wingo et al 9 and Abraiov et al 10 reported in a retrospective study that good results can be obtained by patch closure or aneurysm plication.…”
Section: Discussionmentioning
confidence: 99%
“…Aim of surgical treatment is to preserve the aortic root geometry with normal aortic valve functions [ 6 ] . Primary repair may be applied for small aneurysms; however, resection and patch repair are preferred in bigger cases.…”
Section: Discussionmentioning
confidence: 99%